MANAJEMEN MUTU PENDIDIKAN - Syahril Chaniago (Jurnal Ilmiah Econosains, 2010)
ABSTRACTHeadmaster as a manager, administrator and educator, as the manager of the school, each day is never quiet in the process of problem solving and decision making. Ability to solve problems can be improved and gained, not only through education and training, but can be obtained and experiences during the lead school, independent study, reading books or literature. Principal plays a vital role in the quality of education. Principal increasingly required to enhance the quality of their professionalism in order to improve the quality of output (output) units of work. It is recognized that the education process not only takes place in school, but lasted well beyond the school. However the Head of School is good, very big responsibility in schools and things that can be done in an environment outside of school. Quality education in school is influenced by factors. One of them is the Principal factor managerial influence on the process of education in their schools. Therefore, any attempt to improve / enhance the quality of school management should be viewedas part of a major effort to improve the quality of education.Keywords: Headmaster, manager, management, education